2016
DOI: 10.1039/c5cc07635h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of urea in cometary model ices and implications for Comet 67P/Churyumov–Gerasimenko

Abstract: Urea is considered a fundamental building block in prebiotic chemistry. Its formation on early Earth has not yet been explained satisfactorily and exogenous delivery has been considered. We report on the synthesis along with the first online and in situ identification of urea after exposing inorganic ices to ionizing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Thee nergies are refined by the coupled cluster [28] CCSD(T)/cc-pVDZ with B3LYP/cc-pVTZ zero-point energy corrections.B 3LYP/cc-pVTZ//CCSD(T)/ cc-pVTZ level of calculationare expected to have an accuracywithin 9kJmol À1 . [29] TheG AUSSIAN09 program [30] is used in these electronic structure calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Thee nergies are refined by the coupled cluster [28] CCSD(T)/cc-pVDZ with B3LYP/cc-pVTZ zero-point energy corrections.B 3LYP/cc-pVTZ//CCSD(T)/ cc-pVTZ level of calculationare expected to have an accuracywithin 9kJmol À1 . [29] TheG AUSSIAN09 program [30] is used in these electronic structure calculations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the formation of glycine (Holtom et al 2005), amino acids (Elsila et al 2007), dipeptides (Kaiser et al 2013), hydroxyacetonitrile, aminomethanol and polyoxymethylene (Danger et al 2012(Danger et al , 2014, glycolaldehyde and glyceraldehyde (de Marcellus et al 2015), or alpha-aminoethanol (Duvernay et al 2010) in ice was reported experimentally. Recently, Forstel et al (2016) have synthesized urea in cometary model ices thanks to the irradiation of inorganic ice (which contains CO and NH 3 ), proposing a mechanism in which NH 2 • is added to hydrogenated CO.…”
Section: )mentioning
confidence: 99%
“…The formamide molecule (HCONH 2 ) as detected in the interstellar medium (ISM; Gottlieb et al 1973;Hollis et al 2006;Halfen et al 2011;Adande et al 2013) represents the simplest molecule carrying the amide (peptide) bond (Figure 1). Very recently, Jones et al (2011) elucidated the formation mechanism of formamide in astrophysically relevant ices exposed to energetic electrons via the radical-radical recombination of formyl (HCO) with the amidogen radical (NH 2 ) inside astrophysically relevant ices at 10 K. The next homologue molecule in this series-urea (CO (NH 2 ) 2 )-was also detected in processed ices online and in situ, exploiting photoionization of the subliming molecules during the temperature programmed desorption (TPD) phase via tunable vacuum ultraviolet (VUV) light and by detecting the parent ion through a reflectron time-of-flight mass spectrometer (PI-ReTOF-MS; Förstel et al 2015a) It is also well established that amino acids (Bernstein et al 2002;Munoz Caro et al 2002;Elsila et al 2007;Chen et al 2008;Hudson et al 2008) and their formal condensation products-dipeptides-as complex as Glycylglycine (Gly-Gly) and LeucylAlanine (Leu-Ala) can be synthesized abiotically in energetically processed ices ; Figure 1). Note that formamide (HCONH 2 ) might act as a key intermediate in the synthesis of amino acids (Dederichs et al 1975;Apene & Mikstais 1978;Kostakis et al 2007).…”
Section: Introductionmentioning
confidence: 99%